(untitled) (European Journal of Economics, Finance and Business Development, 2023)
This article focuses on the process of forecasting, which is one of the main directions of economic research. Definitions given by a number of economists to the terms forecast and forecasting were observed and personal opinions expressed by the author. In addition, the importance of econometric models in the process of forecasting is justified, and this is justified by the example of the object selected for research.